Deconstruction of physical fitness assessment system and medical rehabilitation countermeasures for physically disabled teenagers with natural language processing technology - Wang, Dan; Sun, Pu (Frontiers in Public Health, 2022)
Disability is a component of social relations and the existence of social reality. An effective solution to the problem of persons with disabilities is a measure of human civilization and social progress. The strength of the implementation of disability policy is the key to the realization of the original intention of “effectively solving the problem of disabled persons and promoting their development”. The purpose of this paper is to study the physical fitness evaluation system and medical rehabilitation strategies of physically handicapped adolescents with natural language processing technology. It mainly adopts literature research, interview and comparative analysis. Taking the rehabilitation policy for the disabled as the research starting point, the current situation of mental health of physically disabled adolescents will be examined, and the influence of physical exercise attitude and exercise level on mental health will be explored. And by comparing the difference in physical exercise level and mental health of physically handicapped youth and able-bodied youth, the effect of physical exercise on mental health of physically handicapped youth is further explained. This paper selects a total of 760 physically disabled students and able-bodied students from a secondary school as subjects, and uses research methods such as questionnaire survey and computer test to investigate the current situation of mental health of physically disabled adolescents and the relationship between physical exercise and mental health. The experimental results show that the spatiotemporal judgment experiment uses pixel difference as an indicator, and the judgment error of limb residual limbs is significantly larger than that of healthy limbs (p < 0.01). In the span of spatial location memory, the grades of the limb-restrained students were significantly lower than that of the able-bodied students (p < 0.05).